The sperm of Hexagenia (Pseudeatonica) albivitta Walker (Ephemeroptera: Fossoriae: Ephemeridae). (8th January 2014) - Brito, Pedro; Mancini, Karina; Salles, Frederico Falcão; Rizzi, Evandro Apolinario; Dolder, Heidi
Abstract This study describes the sperm morphology of the mayfly Hexagenia (Pseudeatonica) albivitta (Ephemeroptera). Its spermatozoon measures approximately 30 μm of which 9 μm corresponds to the head. The head is composed of an approximately round acrosomal vesicle and a cylindrical nucleus. The nucleus has two concavities, one in the anterior tip, where the acrosomal vesicle is inserted and a deeper one at its base, where the flagellum components are inserted. The flagellum is composed of an axoneme, a mitochondrion and a dense rod adjacent to the mitochondrion. A centriolar adjunct is also observed surrounding the axoneme in the initial portion of the flagellum and extends along the flagellum for at least 2 μm, surrounding the axoneme in a half‐moon shape. The axoneme is the longest component of the flagellum, and it follows the 9+9+0 pattern, with no central pair of microtubules. At the posterior region of the flagellum, the mitochondrion has a dumb‐bell shape in cross sections that, together with the rectangular mitochondrial‐associated rod, is responsible for the flattened shape of the flagellum. An internal membrane is observed surrounding both mitochondrion and its associated structure.